Peran moderasi religiusitas pada pengaruh kesadaran halal, kebiasaan, dan label halal terhadap keputusan pembelian - Nur Safrian Ahmad; Raden Hendri Gusaptono (Journal of Halal Industry Studies, 2026)
This study aims to analyze the influence of halal awareness, habits, and halal labels on purchasing decisions for Kahf products, with Religiosity as a moderating variable. The sampling technique used was non-probability sampling with purposive sampling. Data were collected through an online Google Form questionnaire distributed to 100 respondents. Data analysis was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS. The results showed that Halal Awareness has a positive and significant influence on Purchasing Decisions for Kahf products. Habit also has a positive and significant effect on Purchasing Decisions. In addition, the Halal Label has a positive and significant influence on Purchasing Decisions for Kahf products in Sleman Regency. Religiosity serves as a moderating variable, strengthening the influence of Halal Awareness on Purchasing Decisions. However, Religiosity weakens the influence of Habit on Purchasing Decisions. In addition, Religiosity strengthens the Halal Label's influence on Purchasing Decisions for Kahf products. These findings enrich the development of the Theory of Planned Behavior in the context of halal product consumption by showing that Religiosity does not always strengthen the influence of behavioral determinants but, in certain contexts, can weaken the influence of habits. In practice, companies need to develop differentiated marketing strategies based on consumer religiosity, emphasizing halal education in the high-religiosity segment and habit formation in the low-religiosity segment.